Visual C++6 the complete reference - Pappas, Chris H. 1953- (Osborne McGraw-Hill, 1998)
Comprehensive coverage of Microsoft's Visual C++ 6--includes both expansive reference and tutorial material. Covers both C/C++ programming fundamentals and Windows 98/NT program development. Increased detailed coverage of debugging, C++ objects, COM, ActiveX, and programming with MFC. Both authors are professors of computer science at the S.U.N.Y. system in New York--they know how to teach the subject. Provides new and experienced Visual C++ programmers with up-to-date and complete information in one concise volume.